Financial Implication of COVID-19: A Story of Malaysian Dental Practitioner - Abdul Hamid, Nor Faharina; Jaafar, Azlan; Mohamd Mahmod, Nurul Haini Najwa; Raja Amir Hamzah, Raja Nur Nabiha (UI Scholars Hub, 2021)
Coronavirus disease 2019 (COVID-19) has caused series of lockdown in Malaysia which led to the significant financial impact to dental practitioner in Malaysia. Objectives: The aim of this study is to investigate factors affecting dental practice and its implication to financial situation during the pandemic in Malaysia. Methods: Registered Malaysian dental practitioners were invited to participate in online questionnaire via google form. Descriptive and Pearson’s chi-square test analysis were conducted (p<0.05). Results: 468 of dental practitioners had responded to our survey. More than three-quarter of dental practitioners worked in government sectors while almost a quarter worked in private sectors. 49.2% of respondents opened for emergency cases only during movement control order (MCO), 42.1 % of them limit for dental emergency, appointment-based cases and non-aerosol generated procedure during Conditional MCO and 62.5% operated as usual following a strict standard operating procedure during Recovery MCO. More than three quarter of private dental practitioners indicated that pandemic affected their daily monetary income (p<0.001) while most of them had to spend other source of income (p=0.004). All working sectors dictated that the working volume and number of patients had statistically decrease (p<0.05). Conclusion: COVID-19 pandemic had an impact on the practice of dentistry and financial position especially for private dental practitioners. Major government assistance is important to reduce the burden of dental practitioner and preserving their future practice.